Gender and the Strategic and Tactical Logic of Boko Haram’s Suicide Bombers - Galehan, Jordan N. (Women & criminal justice, 2023)
Boko Haram is well known for its use of women as suicide bombers. While prior research has examined why this phenomenon is occurring, as well as what makes Boko Haram a unique terror group, the present study examines how their female bombers are infiltrating targets, what types of targets are being successfully infiltrated, and whether the bomber’s gender has an impact on the infiltration tactic and the success of the bombing mission. Utilizing the open-sourced data provided by the Global Terrorism Database (GTD), a complementary qualitative dataset was compiled that included 102 female suicide bombing incidents from 2014 to 2017. Results of content analysis indicate that there was a variety of infiltration tactics used by the female bombers that progressively evolved as specific tactics’ effectiveness waned, and that gender impacted the missions allowing for the female bombers to effectively infiltrate soft targets with high casualties, increasing the group’s overall utilization of females in operative roles.